Dinamika Populasi Ternak Kambing Lakor di Kecamatan Lakor Kabupaten Maluku Barat Daya: The Population Dynamics of Lakor Goat Livestock in Lakor, Southwest Maluku Regency - Harmoko; H. Jesajas; J. Makatita; J. M. Lainsamputty; R. L. Dolewikou (Fakultas Peternakan Universitas Papua, 2022)
Abstract This study aims at determining the population dynamics of the Lakor goats raised traditionally by the local community in Lakor District, Southwest Maluku Regency. This study was carried out in Lakor for approximately one month from November to December 2021. The selection of the research location was through purposive sampling. In collecting the data, the researchers applied direct observation (survey), interviews with the breeders using a questionnaire, and documentation. The collected data were in the form of primary and secondary data. In this study, the research variables were the population structure of the Lakor goat, livestock input, livestock output, and natural increase value. The data in this study were tabulated and analyzed using descriptive statistical analysis by utilizing a frequency table and being represented in percent (%). Results showed as follows. Based on the education level of Lakor goat breeders, those who had elementary education reached 46.67%, those having junior high education reached 21.67%, and those having senior high education reached 25.00%. Meanwhile, based on the population dynamics of Lakor goats, the percentage of kid male Lakor goats was 22.96% and that of females was 34.24%, the percentage of adolescent male Lakor goats was 11.06% and that of females was 13.99%, and the percentage of adult male Lakor goats was 8.42% and that of females was 9.32%. Moreover, the input of Lakor livestock was 28.67% from births and 9.88% from purchases. Furthermore, the output of Lakor goats was 6.54% death, 6.96% slaughter, and 14.61% sales, and Natural Increase 22,13%. Keywords: Lakor goat; Livestock input; Livestock output. Abstrak Penelitian dilakukan dengan maksud untuk mengetahui dinamika populasi budidaya ternak kambing Lakor yang dilakukan secara tradisional oleh masyarakat peternak di Kecamatan Lakor Kabupaten Maluku Barat Daya. Penelitian dilaksakanan di Kecamatan Lakor selama kurang lebih bulan yakni November hingga Desember 2021. Penetapan lokasi penelitian dengan menggunakan metode purposive sampling dan pengamatan langsung (survei) pada lokasi dan menggunakan kuesioner sebagai alat bantu untuk mewawancarai para peternak. Tekni pengambilan data penelitian menggunakan tekni observasi, wawancara dan dokumentasi, data penelitian yang dikumpulkan yaitu data primer dan data skunder. Variabel penelitian yaitu struktur populasil kambing Lakor, input ternak, output ternak dan Nilai natural increase. Data hasil penelitian ditabulasikan dan dianalisis menggunakan analisis statistik deskriptif dengan menggunakan tabel frekuensi yang dinyatakan dalam persen (%). Hasil penelitian bahwa tingkat pendidikan peternak kambing Lakor yaitu SDN mencapai 46,67%, peternak dengan pendidikan SMP mencapai 21,67 dan SMA mencapai 25,00%. Sedangkan data dinamika populasi ternak kambing Lakor bahwa persentase anakkan kambing Lakor jantan 22,96% dan betina 34,24%, persentase kambing Lakor mudah jantan 11,06% dan betina 13,99%, dan persentase kambing Lakor dewasa jantan 8,42% dan betina 9,32%, Input ternak Lakor berasal kelahiran 28,67% dan pembelian 9,88%, output ternak kambing Lakor yaitu kematian 6,54%, pemotongan 6,96% dan penjualan 14,61%, dan nilai Natural Increase 22,13%. Kata Kunci: Input ternak; Kambing lakor; Output ternak